(untitled) (Revista da Escola de Guerra Naval, 2023)
The National Security Strategy (NSS) are specific documents prepared periodically by the United States’ executive, describing the main concerns of Americans’ national security and developing strategies to face the challenges. At the same time, by exposing the US government’s strategic vision, it contributes to informing the US government’s approach and intent on various topics related to security and foreign policy. This paper seeks to analyze the NSS of the last four American presidents, in a time frame that runs from the immediate post-Cold War to Trump’s administration, as well as its influences with regard to Latin America. Using a quantitative method, through the frequency content analysis, and a qualitative methodology, based on the empirical-deductive method, the central objective is to rationalize that, although there was a relative power vacuum at the beginning of the 21 st century, there is a return of the region as an important geopolitical and geoeconomic space in contemporary times.